(untitled) - Shaffer, Ron (Ames, 1989)
The main body of economic research and literature has neglected the economics of smaller communities. Community Economics: Linking Theory and Practice fills that information void. This text serves as a comprehensive guide on smaller, open economies and urban neighborhoods for economists, regional planners, rural sociologists, and geographers. Additionally, Community Economics is an issue-oriented handbook of development strategies for development practitioners, planning and zoning officials, and others involved in the ay-to-day activities of community economic development.
Keywords: Regional economics,Economic development,Economic geography,Khu vực kinh tế,Phát triển kinh tế,Địa lý kinh tế